2011
DOI: 10.1007/s11814-011-0075-8
|View full text |Cite
|
Sign up to set email alerts
|

Gas transport behavior of DMDCS modified MCM-48/polysulfone mixed matrix membrane coated by PDMS

Abstract: Mesoporous MCM-48 silica was synthesized by templating method and the structure of particles was characterized by XRD, TEM and N 2 adsorption techniques. The surface modification of particles in order for introducing into PSF matrix was performed by dimethyldichlorosilane (DMDCS) silylation agent. SEM images of as-synthesized and modified MCM-48/PSF MMMs indicate that in the modified MCM-48 silica particles adhered well to the PSF matrix and that the synthesized MMMs were defect free. The incorporation of MCM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…Moreover, all the coated samples show an increase permeance for CO 2 and selectivity compared to the neat. Several studies have reported similar improvement on the gas transport properties upon coating and heat treatment [21,22]. …”
Section: Effect Of Membrane Coatings On Gas Permselectivitymentioning
confidence: 80%
“…Moreover, all the coated samples show an increase permeance for CO 2 and selectivity compared to the neat. Several studies have reported similar improvement on the gas transport properties upon coating and heat treatment [21,22]. …”
Section: Effect Of Membrane Coatings On Gas Permselectivitymentioning
confidence: 80%
“…The nitrogen adsorption–desorption isotherm of KIT-6 is shown in Figure 4. From the nitrogen adsorption isotherms of KIT-6, type IV with a hysteresis loop can be observed which proved the characteristic of a mesoporous material [15,16,19,22,24]. The specific surface area, pore volume, and pore diameter of KIT-6 were determined to be 585 m²/g, 0.42 cm³/g, and 7.01 nm, respectively, which agreed with the data reported by Kishor & Ghoshal [22].…”
Section: Resultsmentioning
confidence: 94%
“…Kim and Marrand [18] reported that incorporation of 40 wt % of MCM-41 into PSF increased the CO 2 permeability by 275% compared to pristine PSF. Jomekian et al [19] prepared the MMMs of PSF incorporated with MCM-48 increased the CO 2 permeability by ~193% compared to pristine PSF. These studies show that incorporation of mesoporous silica into polymer membranes could enhance the gas permeability of the membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the nitrogen adsorption–desorption isotherms of KIT-6 and NH 2 KIT-6. Type IV with a hysteresis loop from the nitrogen adsorption isotherms for KIT-6 and NH 2 KIT-6 is observed, which represents the characteristic of a mesoporous material [ 4 , 5 , 20 , 26 ]. According to the IUPAC classification, a type H1 hysteresis loop can be observed from the isotherm; this indicates the characteristic of mesoporous materials and characteristic of material with interconnected large cylindrical pore geometry and a high degree of pore size uniformity [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Membrane technology exhibits operational flexibility, small design, cost efficiency, easy scale-up, high product quality, and a small footprint [ 1 , 2 , 3 ]. However, polymer membranes commonly suffer from a trade-off between permeability and selectivity [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%